2017
DOI: 10.3390/ijms18050957
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Fragaria ananassa Crude Extract on Cadmium-Induced Lipid Peroxidation, Antioxidant Enzymes Suppression, and Apoptosis in Rat Testes

Abstract: Cadmium is a deleterious environmental pollutant that threats both animals and human health. Oxidative stress and elevated levels of reactive oxygen species (ROS) have recently been reported to be the main cause of cellular damage as a result of cadmium exposure. We investigate, here, the protective effect of strawberry crude extracts on cadmium-induced oxidative damage of testes in rats. Four groups (n = 8) of 32 adult male Wistar rats weighing 160–180 g were used. The control group received 0.9% saline solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 47 publications
7
41
0
1
Order By: Relevance
“…The results are consistent with the findings of Navaneethan and Rasool [52]. Additionally, Elmallah et al [53] reported that Cd stress significantly decreased antioxidant enzymes SOD and CAT in rat liver.…”
Section: Discussionsupporting
confidence: 90%
“…The results are consistent with the findings of Navaneethan and Rasool [52]. Additionally, Elmallah et al [53] reported that Cd stress significantly decreased antioxidant enzymes SOD and CAT in rat liver.…”
Section: Discussionsupporting
confidence: 90%
“…Oral administration of different strawberry extracts down-regulated the expression of TNF-α in nicotinamide–streptozotocin-induced diabetes in rats [ 57 ]. Furthermore, we previously showed that the methanolic extract of strawberry effectively attenuated cadmium-induced inflammation in liver [ 21 ], kidney [ 5 ], and testis [ 22 ] tissues. Our findings showed that compared with Cd-intoxicated rats, rats treated with SME showed down-regulation of TNF-α expression in the brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the extract has high concentration of total phenolics content ranged from 98.3 to 112.7 mg/g extract, total flavonoids content ranged from 44.2 to 57.1 mg/g extract, and the total anthocyanin content ranged from 12.6 to 25.3 mg/g extract [ 21 ]. These bioactive compounds provide health benefits through several mechanisms, including the scavenging of ROS, protecting and regenerating other dietary antioxidants, and chelation of pro-oxidant metals [ 22 ]. These active ingredients have various pharmacological activities such as prevention of inflammation, hepatotoxicity, cancer, obesity, and oxidative stress [ 21 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, Cd induced oxidative damage by increased lipid peroxidation and inhibitions of enzymes required to prevent such oxidative damage. Similar results showed by many previous study [76][77][78][79][80][81] . Cd generate free radicals and ROS such as H2O2, superoxide O2( -) and hydroxyl radical (OH -), nitric oxide (NO -)3 and can reduce the level of the main antioxidant compounds in the cells by inactivating enzymes and other antioxidant molecules 82 .…”
Section: Histopathological Examination Of Testessupporting
confidence: 81%